2018
DOI: 10.14236/ewic/hci2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Navigation: a Comparison Between the Free Exploration of a Real and a Virtual Museum

Abstract: The validity of environmental simulations resides in their capacity to replicate responses produced in a physical environment. However, no studies validate the similarity of navigation in immersive virtual environments, even though this can radically condition space perception and therefore alter the various evoked responses. The objective of this present paper is to validate environmental simulations using 3D environments and head-mounted display devices, at perception level by means of presence and at behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Perceptual quality of these environments could be enhanced by using advanced numerical data, such as chromaticity and spectral data [42]. Virtual reality was used to evaluate qualitative effect of complex sunlight patterns [43]. A study on lighting features in various virtual environments demonstrated that virtual reality is the closest to physical space, in comparison to video and photograph reproductions [44].…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual quality of these environments could be enhanced by using advanced numerical data, such as chromaticity and spectral data [42]. Virtual reality was used to evaluate qualitative effect of complex sunlight patterns [43]. A study on lighting features in various virtual environments demonstrated that virtual reality is the closest to physical space, in comparison to video and photograph reproductions [44].…”
Section: Introductionmentioning
confidence: 99%